Nursing of a patient with nocturia treated by auricular acupoint sticking and pressing therapy (耳穴贴压治疗1例夜尿症患者的护理体会) - DONG Huaqian (董画千); XIE Wei (谢薇); CHEN Xiaoqiong (陈晓琼); HE Yanling (何燕琳); REN Xiuya (任秀亚); YUAN Dan (袁丹) (Association of Integrative Nursing, 2022)
Nocturia is one of the common clinical symptoms of lower urinary tract, with a high incidence, which not only seriously affects patients' sleep quality and quality of life, but also increases risk of complications due to frequent night awakenings. This article reported a patient with nocturia treated by auricular acupoint sticking and pressing therapy. Experience of auricular acupoint selection by syndrome differentiation, operation method and basic nursing measures were summarized. auricular acupoint sticking and pressing therapy is an easy-to-operate, safe and effective therapy for nocturia. (夜尿症不仅严重影响患者睡眠, 降低生活质量, 还可能导致一系列并发症的发生。本文总结1例耳穴贴压疗法治疗夜尿症患者的相关护理经验, 包括辨证选穴、耳穴贴压操作方法、基础护理等, 耳穴贴压疗法操作简单、安全环保, 不仅能有效缓解夜尿症症状, 且患者接受度较高。)